hiPSC-Based Model of Prenatal Exposure to Cannabinoids: Effect on Neuronal Differentiation - Miranda, Cláudia C.; Barata, Tiago; Vaz, Sandra H.; Ferreira, Carla; Quintas, Alexandre; Bekman, Evguenia P. (Frontiers in Molecular Neuroscience, 2020)
Phytocannabinoids are psychotropic substances ofcannabis with the ability to bind endocannabinoid (eCB) receptors that regulate synaptic activity in the central nervous system (CNS). Synthetic cannabinoids (SCs) are synthetic analogs of Δ9-tetrahydrocannabinol (Δ9-THC), the psychotropic compound of cannabis, acting as agonists of eCB receptor CB1. SC is an easily available and popular alternative to cannabis, and their molecular structure is always changing, increasing the hazard for the general population. The popularity of cannabis and its derivatives may lead, and often does, to a child’s exposure to cannabis both in utero and through breastfeeding by a drug-consuming mother. Prenatal exposure to cannabis has been associated with an altered rate of mental development and significant changes in nervous system functioning. However, the understanding of mechanisms of its action on developing the human CNS is still lacking. We investigated the effect of continuous exposure to cannabinoids on developing human neurons, mimicking the prenatal exposure by drug-consuming mother. Two human induced pluripotent stem cells (hiPSC) lines were induced to differentiate into neuronal cells and exposed for 37 days to cannabidiol (CBD), Δ9-THC, and two SCs, THJ-018 and EG-018. Both Δ9-THC and SC, at 10 μM, promote precocious neuronal and glial differentiation, while CBD at the same concentration is neurotoxic. Neurons exposed to Δ9-THC and SC show abnormal functioning of voltage-gated calcium channels when stimulated by extracellular potassium. In sum, all studied substances have a profound impact on the developing neurons, highlighting the importance of thorough research on the impact of prenatal exposure to natural and SC.